Mission and Commission of Christ - Pushparajan, A (Journal of Dharma, 1981)
Formerly Christianity was supposed to be in opposition to other religions, as truth to falsehood, light to darkness and so on. Even when ’good’ and ’holy’ elements were found in other religions, they were only to be ’rescued’ from the native surroundings which were necessarily corruptive, and be brought into the Church in order that they be conserved in the Church and be consecrated to the Lord Jesus, the fulfiller of all the religious longings of men. Naturally, therefore, the great commission of Christ in Mt. 28, 19-20 was given the most straightforward interpretation. And organized efforts were made, in all possible ways, to proclaim the Gospel throughout the yorld and implant the Church wherever possible. Recently, however, it has become a general practiœ among Christians to accept the non-Christian religions also as valid means of salvation.